Improvement control of photovoltaic based water pumping system without energy storage. (15th September 2019) - Errouha, Mustapha; Derouich, Aziz; Nahid-Mobarakeh, Babak; Motahhir, Saad; El Ghzizal, Abdelaziz
Highlights: A simple standalone PV water pumping system based on an IM is presented. Energy optimization and losses minimization of the IM using the proposed method. Hardware implementation of the proposed control strategy using dSpace DS1005 board. Abstract: This paper presents a simple standalone photovoltaic (PV) water pumping system (PVWPS) based on an induction motor (IM) without the use of chemical energy storage. The aim of this paper is improving the control performance of pumping system. The proposed method is based on an indirect field-oriented control (IFOC) which consists of operating the motor at optimum flux by minimizing the induction motor losses. Perturb ad observe (P&O) algorithm is used to extract the maximum possible power from the PV panel. The performance of the proposed approach is proved by real time implementation using a dSpace DS1005 system and compared with conventional IFOC without losses minimization. Results show that using the proposed method, the losses are reduced and the efficiency is increased by 12%, 2.5% and 5% under 375 W/m 2, 750 W/m 2 and daily profile respectively.